Inactive Matrix Gla Protein and Cardiovascular Outcomes: The Multi‐Ethnic Study of Atherosclerosis - Ashley A. Berlot; Xueyan Fu; M. Kyla Shea; Russell Tracy; Matthew Budoff; Ryung S. Kim; Mahim Naveed; Sarah L. Booth; Jorge R. Kizer; Anna E. Bortnick (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background MGP (matrix Gla protein) inhibits arterial calcification. Higher inactive MGP, in its dephosphorylated‐uncarboxylated (dp‐uc) form, is positively associated with vascular calcification, possibly portending adverse cardiovascular events. The objective of this study was to determine the association of dp‐ucMGP with incident cardiovascular disease (CVD) events and mortality in MESA (Multi‐Ethnic Study of Atherosclerosis). Methods MESA is a prospective cohort study of 45‐ to 84‐year‐old individuals enrolled between 2000 and 2002 with adjudicated outcomes through 2019. Dp‐ucMGP was measured at baseline in n=2663 participants with cardiac computed tomography at Exams 1 (2000–2002) and 5 (2010–2012). Age‐stratified Cox proportional hazard models were used to assess dp‐ucMGP with risk of all CVD (mean follow‐up 16±4 years), hard CVD (17±3 years), hard coronary heart disease (17±3 years), and all‐cause mortality (18±2 years). Results The youngest age quartile (45‐ to 53‐years‐old) with higher dp‐ucMGP levels (520–2934 pmol/L) had an increased risk of all CVD (hazard ratio [HR], 3.05 [95% CI, 1.58–5.90], P=0.001), hard CVD (HR, 2.85 [95% CI, 1.30–6.23], P=0.009), hard coronary heart disease (HR, 3.79 [95% CI, 1.31–10.95], P=0.014), and all‐cause mortality (HR, 2.73 [95% CI, 1.19–6.30], P=0.018) compared with those with dp‐ucMGP levels between 150 and 519 pmol/L in maximally adjusted models. Conclusions Younger individuals 45 to 53 years old with elevated dp‐ucMGP levels (≥520 pmol/L) had an increased risk of incident CVD, coronary heart disease, and all‐cause mortality. No association was seen in older adults. Additional studies are needed to better delineate the relationship of inactive MGP with incident CVD, coronary heart disease, and all‐cause mortality.